Analysis of Major Known Driver Mutations and Prognosis in Resected Adenosquamous Lung Carcinomas - Wang, Rui; Pan, Yunjian; Li, Chenguang; Zhang, Huibiao; Garfield, David; Li, Yuan; Ye, Ting; Hu, Haichuan; Luo, Xiaoyang; Li, Hang; Zhang, Yang; Zhang, Jie; et al. (Journal of thoracic oncology, 2014)
Genotyping for driver mutations is now routinely used to guide clinical care of patients with lung cancer. Adenosquamous lung carcinoma (AdSqLC) is a subtype of cancer that contains both adenocarcinoma and squamous cell carcinoma. However, the incidence, clinicopathologic characteristics, and prognostic implications of major driver mutations in AdSqLCs are not well established. Seventy-six resected AdSqLCs and 646 lung adenocarcinomas were screened for known genetic alterations involving EGFR, ERBB2, KRAS, BRAF, PIK3CA, AKT1, RET, and ALK. Tumors showing acinar, lepidic, micropapillary, or papillary growth in glandular component were classified as classical AdSqLC. Of the 76 AdSqLCs, 43 (56.6%) harbored known mutant kinases, including 24 (31.6%) with EGFR mutations, eight (10.5%) with KRAS mutations, two (2.6%) with AKT1 (2.6%) mutations, one (1.3%) with ERBB2 insertion mutation, one (1.3%) with PIK3CA mutation, four (5.3%) with ALK fusions, and three (4%) with KIF5B-RET fusions. No mutation was found in BRAF. The mutational profiles and clinicopathologic characteristics of classical AdSqLC were strikingly similar to that of poorly differentiated adenocarcinoma. However, AdSqLCs with solid growth pattern in glandular component had high frequency of ALK or RET fusions and low EGFR mutation rate. To our knowledge, this is the first comprehensive study investigating major oncogenic driver mutations in a large cohort of AdSqLC patients in a Chinese population. The findings suggest that it will be clinically valuable to investigate the growth pattern of glandular component in AdSqLCs.